Outer Retinal Structure in Best Vitelliform Macular Dystrophy - Kay, David B. (2013)
OBJECTIVE: To characterize outer retinal structure in Best Vitelliform Macular Dystrophy (BVMD), using spectral domain optical coherence tomography (SD-OCT) and adaptive optics scanning light ophthalmoscopy (AOSLO). METHODS: Four symptomatic members of a family with BVMD with known BEST1 gene mutation were recruited. Thickness of two outer retinal layers corresponding to photoreceptor inner and outer segments were measured using SD-OCT. Photoreceptor mosaic AOSLO images within and around visible lesions were obtained, and cone density was assessed in two subjects. RESULTS: Each subject was at a different stage of BVMD, with photoreceptor disruption evident by AOSLO at all stages. When comparing SD-OCT and AOSLO images from the same location, AOSLO images allowed for direct assessment of photoreceptor structure. A variable degree of retained photoreceptors was seen within all lesions. The photoreceptor mosaic immediately adjacent to visible lesions appeared contiguous and was of normal density. Fine hyperreflective structures were visualized by AOSLO, and their anatomical orientation and size are consistent with Henle fibers. CONCLUSIONS: AOSLO findings indicate substantial photoreceptor structure persists within active lesions, accounting for good visual acuity in these patients. Despite previous reports of diffuse photoreceptor outer segment abnormalities in BVMD, our data reveal normal photoreceptor structure in areas adjacent to clinical lesions. CLINICAL RELEVANCE: This study demonstrates the utility of AOSLO for understanding the spectrum of cellular changes that occur in inherited degenerations such as BVMD. Photoreceptors are often significantly affected at various stages of inherited degenerations, and these changes may not be readily apparent with current clinical imaging instrumentation.